HUBUNGAN PENGETAHUAN, SIKAP, DAN BUDAYA DENGAN PERILAKU PENGGUNAAN AIR SUNGAI (Studi Di Wilayah Kerja Puskesmas Martapura 2) - Sharah Monica (The Indonesian Journal of Public Health, 2018)
Diarrhea is one of the most common infectious diseases. It has related three factors such ass environment, food and contact with an infected person. One of the environmental factor of diarrhea is the domestic water use behavior. The main objective of this study was to analyse the relation between knowledge, atitude  and habit to  domestic water use behavior in  Martapura 2 Public Health Center, work area Pasayangan Selatan Village, sub-district of Martapura, Banjar, South Kalimantan Province. Case control study design was used in this study. The population of the study were all diarrhea patients in Martapura 2 Public Health Center work area  from february 2017 until february 2018. The Lemeshow was used to determine research sample size. The study sample consisted of 45 case diarrhea patients and 45 control non diarrhea patient. Samples were taken from all eligible cases and controls on specified inclusion and exclusion criteria. Data will analysed use Chi Square. Based on the results of this study comparing between case group and control group, most of the respondents in the case group have knowledge in poor knowledege was  25 people (55.6%) and the control group in good knowledge that was 35 people (77.8) with Chi Square, all p < 0,001. Attitudes of respondents in the case group were in the not good category is 26 people (58.0%) and control group in good category that was 32 people (71,1%) with (p value 0,000 in case and control 0,004). Utilitation habit respondents in the case group were in the non-existent category of 26 persons (57.8%) and the control group in the category of no 37 people (82.2%) with (p value in case 0.006 and control 0.000). Conclusively, the variable of knowledge, attitude  and habit have very significant relation on the group of case and control.